Stressors and coping strategies of state university students in a developing country - Kasayira, Joseph M.; Chipandambira, Kudzai S.; Hungwe, Chipo; Mupawose, Anniah (Journal of Psychology in Africa, 2016)
The study examined stressors and coping strategies of 281 Social Sciences students at the Midlands State University in Zimbabwe (49% female, 51% male). A questionnaire was used to collect data. The results showed that the 7 most common stressors were: finance, reading resources, accommodation, food, transport, inadequate infrastructure and lecturer related problems. The students mentioned 34 coping strategies that were categorized and then analysed for effectiveness. The effects of sex, residence status and academic year differences were evaluated using Mann Whitney U test and Kruskal-Wallis rank order analysis of variance. There were no significant differences in coping strategies for stressors by demographic variables.